2014
DOI: 10.1140/epja/i2014-14167-9
|View full text |Cite
|
Sign up to set email alerts
|

Density and temperature in heavy-ion collisions: A test of classical and quantum approaches

Abstract: Different methods to extract the temperature and density in heavy ion collisions are compared using a statistical model tailored to reproduce many experimental features at low excitation energy. The model assumes a sequential decay of an excited nucleus and a Fermi gas entropy. We first generate statistical events as function of excitation energy but stopping the decay chain at the first step. In such a condition the 'exact' model temperature is determined from the Fermi gas relation to the excitation energy. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…• It has been also demonstrated that the predicted generation of charged pion condensation by chiral isospin imbalance in dense and cold (T = 0) quark matter remains valid even at the temperatures as high as several dozens or even a hundred MeV. These conditions are rather pertinent in proto-neutron stars [53], supernovae [54] and neutron star mergers [55] as well as in heavy ion collisions [56].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…• It has been also demonstrated that the predicted generation of charged pion condensation by chiral isospin imbalance in dense and cold (T = 0) quark matter remains valid even at the temperatures as high as several dozens or even a hundred MeV. These conditions are rather pertinent in proto-neutron stars [53], supernovae [54] and neutron star mergers [55] as well as in heavy ion collisions [56].…”
Section: Discussionmentioning
confidence: 97%
“…4 (middle and right panels) one can see that PC d phase persists up to T = 0.2m − 0.35m respectively, which are comparatively high temperatures (if one consider m to be constituent quark mass value in vacuum around 300 MeV, then PC d phase corresponds to temperatures as high as 100 MeV). This part of phase diagram is rather ineresting because these conditions are realized in various physical scenarios such as in just born neutron stars (proto-neutron stars) [53], supernovae [54] and neutron star mergers [55] as well as in heavy ion collisions [56].…”
Section: Phase Structure At T =mentioning
confidence: 99%
“…To further investigate the particle emission time effects on the 7'MqF for different temperatures and particles, we display the 7MqF that were derived from protons, tritons, 034617-2 [39] also studied the deexcitation of an excited nucleus using the GEMINI model which assumes a sequential decay of an excited nucleus. They found that the momentum fluctuation temperature shifts down due to the sequential decay.…”
Section: Resultsmentioning
confidence: 99%
“…The situation is less clear at lower bombarding energies, E Lab <1 GeV/A [2]. Widely used methods to extract temperatures in HICs include the analysis of momentum spectra [3][4][5], chemical compositions [6,7], fluctuation observables [8][9][10] and electromagnetic radiation which can, in principle, penetrate out from deeper in the medium [11,12]. Under conditions where thermalization is questionable, coarsegraining method of microscopic transport calculations have been employed, by discretizing the medium evolution into finite spatial cells and time steps, see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an update to QMD called Isospin dependent Quantum Molecular Dynamics (IQMD) which improves upon QMD by taking into account the spin of the nucleons (and including Pauli blocking) [17]. Here we employ a version of QMD transport that implements Pauli blocking yet supplies microscopic information about the nucleons throughout the collision, referred to as Constrained Molecular Dynamics (CoMD) [10,26]. In particular, CoMD achieves a fair description of the ground-state properties of nuclei which is relevant for the initial state of the collision.…”
Section: Introductionmentioning
confidence: 99%